Structuring the Space: A Study on Enriching Node-Link Diagrams with Visual References - Alper, Basak; Henry Riche, Nathalie; Hollerer., Tobias (CHI '14 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2014)
Exploring large visualizations that do not fit in the screen raises orientation and navigation challenges. Structuring the space with additional visual references such as grids or contour lines provide spatial landmarks that may help viewers form a mental model of the space. However, previous studies report mixed results regarding their utility. While some evidence showed that grid and other visual embellishments improve memorability, experiments with contour lines suggest otherwise. In this work, we describe an evaluation framework to capture the impact of introducing visual references in node-link diagrams. We present the results of three controlled experiments that deepen our understanding on enriching large visualization spaces with visual structures. In particular, we provide the first tangible evidence that contour lines have significant benefits when navigating large node-link diagrams.